A scoping review of medical education research in family medicine - Webster, Fiona; Krueger, Paul; MacDonald, Heather; Archibald, Douglas; Telner, Deanna; Bytautas, Jessica; Whitehead, Cynthia (Université d'Ottawa | University of Ottawa, 2015)
Abstract Background Little is known about the state of education research within family medicine. As family medicine education models develop, it is important to develop an understanding of the current state of this research and develop ways to advance the field. Methods We conducted a scoping review of family medicine education research to describe 1) research topic areas and 2) the methodologies and methods used to study these topics. MEDLINE, Social Sciences Abstracts and ERIC electronic databases were searched. 817 full text articles from 2002 to 2012 were screened; 624 articles were included in the review. Results The following research topic areas were identified: continuing education, curriculum development, undergraduate education, teaching methods, assessment techniques, selection of entrants, non-clinical skills, professional and faculty development, clinical decision-making and resident well-being. Quantitative studies comprised the large majority of research approaches; overall minimal methodological details were provided. Conclusions Our review highlights an overall need for increased sophisticated in methodological approaches to education research in family medicine, a problem that could be ameliorated by multiple strategies including better engagement of methodologists throughout the research process. The results provide guidance for future family medicine education research programs.